Multisystem Inflammatory Syndrome in Children in February 2020 and Implications of Genomic Sequencing for SARS-CoV-2. (18th December 2020) - Parsons, Emily; Timlin, Matthew; Starr, Clarise; Fries, Anthony; Wells, Ronald; Studer, Matthew; Sainato, Rebecca
Abstract: Multisystem inflammatory syndrome in children (MIS-C) is a newly recognized disease process that can complicate severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. We present what we believe to be the earliest case of MIS-C, occurring in February 2020. Our patient's SARS-CoV-2 infection was caused by an emerging lineage with the D614G variant in the spike protein. This lineage would subsequently become the predominant cause of SARS-CoV-2 outbreaks in Europe and the United States where MIS-C was first described.